2022
DOI: 10.1123/jsep.2021-0018
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Individual Exercise and Sport Counseling Based on Motives and Goals: A Randomized Controlled Trial

Abstract: This study tested the effectiveness of individual exercise and sport counseling in a nonclinical setting. The COunseling based on Motives and goals in Exercise and sporT (COMET) approach focuses on individual motives and goals and aims to identify suitable activities. Participants experience different exercise and sport activities and reflect on them with a counselor, who applies motivational interviewing. A stratified randomized controlled design with 129 people was used. The intervention group took part in a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 52 publications
2
9
1
Order By: Relevance
“…Although the present study revealed medium effects of the exercise programme on motivational competence, they remained non-significant, probably influenced by our rather small sample size. However, compared to a previous study with less active, healthy adults (Schorno et al, 2022), this research revealed slightly smaller treatment effects. One can speculate that this is related to differences in characteristics in the study population or the delivery mode of the individual exercise counselling.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…Although the present study revealed medium effects of the exercise programme on motivational competence, they remained non-significant, probably influenced by our rather small sample size. However, compared to a previous study with less active, healthy adults (Schorno et al, 2022), this research revealed slightly smaller treatment effects. One can speculate that this is related to differences in characteristics in the study population or the delivery mode of the individual exercise counselling.…”
Section: Discussioncontrasting
confidence: 98%
“…Of note, the effects were not only short-term, but persisted until the follow-up assessment three months after completion of the programme. This means that the intervention empowered participants to apply training-specific knowledge and effectively select and structure activities for (Schorno et al, 2022), individuals with obesity (Göhner et al, 2012), and bariatric surgery patients (Bond et al, 2016), which also revealed medium to high treatment effects on related volitional outcomes. However, the present findings at the follow-up assessment three months after completion of the programme looked somewhat different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to sociocultural factors, the motivational factors that support the development of obligatory exercise behavior are also worth mentioning. Recent literature has demonstrated that motivation appears to be an important factor in influencing physical activity and that young people’s attitudes toward physical and sporting activity will influence motivation and excessive physical activity intake ( 37 ). Pritchard and Beaver ( 15 ) showed that exercise motivation can predict obligatory exercise of young people, and the gender difference is noticeable, improved body tone, enjoyment, and perceived attractiveness predict the obligatory exercise of men, and improved body tone, fitness, and enhanced mood predict the obligatory exercise of women.…”
Section: Introductionmentioning
confidence: 99%
“…All human physical activities are driven and controlled by motivation (36). In addition to sociocultural factors, the motivational factors that support the development of obligatory exercise behavior are also worth mentioning.…”
mentioning
confidence: 99%